(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2012)
The Yoga Sutras is an ancient text that was recorded in India more than 1,000 years ago. It contains the 8-limb path. The 8-limb path describes various prohibitions and requirements for reaching peace and fulfillment. On this 8-limb path, the second limb, Niyama, teaches that looking at life through a virtuous filter can be of benefit. Niyama literally means observances. Yoga Sutra is revived by its application to Alternative Dispute Resolution (ADR).